2010
DOI: 10.1186/1471-2105-11-s6-s12
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme structure dynamics of xylanase I from Trichoderma longibrachiatum

Abstract: BackgroundEnzyme dynamics has recently been shown to be crucial for structure-function relationship. Among various structure dynamics analysis platforms, HDX (hydrogen deuterium exchange) mass spectrometry stands out as an efficient and high-throughput way to analyze protein dynamics upon ligand binding. Despite the potential, limited research has employed the HDX mass spec platform to probe regional structure dynamics of enzymes. In particular, the technique has never been used for analyzing cell wall degradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Protein intrinsic dynamics has been more and more recognized as an important consideration for protein functions [ 1 ]. Several recent studies have revealed that protein dynamics plays essential roles in the catalysis and other functions [ 1 , 2 ]. Among the different techniques, HDX mass spectrometry stands out as a relatively high throughput platform to probe the backbone dynamics of the proteins [ 3 - 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Protein intrinsic dynamics has been more and more recognized as an important consideration for protein functions [ 1 ]. Several recent studies have revealed that protein dynamics plays essential roles in the catalysis and other functions [ 1 , 2 ]. Among the different techniques, HDX mass spectrometry stands out as a relatively high throughput platform to probe the backbone dynamics of the proteins [ 3 - 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…A mixed reality surgical simulator with a VICON motion tracking system, developed for the rasping procedure in artificial cervical disc replacement surgeries is described by Tansel Halic et al , which can serve as an important training and practice tool for surgeons [ 50 ]. The potential of using hydrogen deuterium exchange (HDX) mass spectrometry for analyzing enzymes that degrade cell walls is explored by Uzuner et al [ 51 ]. They report that the HDX mass spectrometry can be a powerful tool for exploring the molecular mechanisms of enzyme functions.…”
Section: Genomic Analysismentioning
confidence: 99%
“…The 3D structures of several thermophilic and mesophilic xylanases including Trichoderma longibrachiatum (Uzuner et al, 2010), Aspergillus niger 400264 xylanase XYNB (Xie et al, 2011), and Aspergillus kawachii (Fushinobu et al, 1998) have been studied. This provides valuable information on correlation between 3D structures and stability of xylanases.…”
Section: Introductionmentioning
confidence: 99%